Utilization of Aloe Vera (Aloe Vera) As a Natural ZPT Alternative For The Growth of Rose Plant Roots - Wilda Rizkiyahnur Nasution; Putri Rizky Hafifah Batubara; Devi Masittah Sigalingging; Lukman Hakim Hasibuan (Bioedunis Journal, 2023)
The Aloe vera plant contains enzymes, minerals, sugars, fatty acids, and also growth hormones, namely auxin and gibberellins. This research was conducted to determine the effect of Aloe vera gel on the growth of rose plants. This research was conducted by giving two different treatments in the form of watering rose plants with Aloe vera gel at several different concentrations and control as a reference. The treatment was carried out for 7 days and then the growth of the rose plants was observed every day. Processing of the data obtained was tested using descriptive analysis. The results showed that at a gel concentration of 10% the rose plants had very different growth and roots compared to the untreated rose plants.